Phytoremediation of Aquaculture Wastewater: Duckweed (Lemna minor L.) as a Phytoremediator - Davies R. M.; Kari W.; Davies O.A. (International Journal of Pollution: Prevention & Control, 2025)
Aquaculture systems discharge huge quantities of waste into the aquatic ecosystem, in the form of excretory products and excess feed. These have grave implications on physicochemical and biological quality of the receiving environment. The study aimed to determine potential of duckweed (Lemna minor L.) for phytoremediation of aquaculture effluent. Hundred grams (100 g) of duckweed was grown in 10 L aquaculture effluent for 7-, 14-, 21-, and 28-day retention period in 15-L plastic containers. Effluent samples were analyzed for some physicochemical parameters (phosphate, nitrate, ammonia, chemical oxygen demand, electrical conductivity, total dissolved solids, and pH). The evaluations were conducted using established and recognized methodologies. The characterization of aquaculture effluent revealed high pollution level. It was found that duckweed reduced aquaculture effluent pollution concentration load to a great extent. Nitrate, ammonia-nitrogen, chemical oxygen demand, and pH were within permissible limits. Discharging aquaculture effluent without prior treatment will be detrimental to the environment and water bodies. This study evaluates the phytoremediation potential of duckweed (Lemna minor L.) for treating aquaculture wastewater. Duckweed was cultivated in aquaculture effluent for varying retention periods (7–28 days) in controlled conditions. Physicochemical analyses of the effluent showed significant reductions in pollutants such as phosphate (68.92%), nitrate (66%), ammonia-nitrogen (79.11%), and chemical oxygen demand. While pH levels were stabilized within permissible limits, electrical conductivity and total dissolved solids exceeded acceptable thresholds for drinking and domestic use. The findings highlight duckweed's cost-effective and sustainable utility for mitigating aquaculture effluent pollution, supporting environmental conservation and resource management.
Keywords: aquaculture; bioremediation; effluent; macrophytes; physicochemical parameters